Entanglement of a Scattered Single Photon and an Exciton - Giang, Nguyen Duc; Van, Tran Thi Thanh; Thanh, Ngo Van; Viet, Nguyen Ai (Communications in Physics, 2009)
A single photon which is initially uncorrelated with an exciton will evolve to be entangled with the exciton on their continuous kinetic variables in the process of resonant scattering. We find the relations between the entanglement and their physical control parameters, which indicates that high entanglement can be reached by changing specific parameters of exciton.